Whole‐Cell Teabag Catalysis for the Modularisation of Synthetic Enzyme Cascades in Micro‐Aqueous Systems. Issue 4 (3rd March 2014) - Wachtmeister, Jochen; Jakoblinnert, Andre; Kulig, Justyna; Offermann, Heike; Rother, Dörte
Abstract Combining enzymes to form multi‐step enzyme cascades has great potential to replace existing chemical routes with high atom‐efficient and eco‐efficient synthesis strategies as well as to grant access to new products, especially those with multi‐stereogenic centres. However, easy solutions and tools for setting up appropriate reaction conditions and process modes are hardly available. The utilisation of teabags filled with whole cells has several advantages, such as 1) simplified handling and recovery of catalyst, 2) easy combination of various catalysts from catalyst toolboxes, 3) fast testing of different operating modes during cascadation and 4) simplified downstream processing. One of the main advantages is that lyophilised whole‐cell catalysts can be applied in micro‐aqueous media, allowing high substrate loads (also of poorly water‐soluble substrates) and concomitantly enabling high catalyst stability. This was demonstrated herein for a synthetic two‐step cascade towards chiral 1, 2‐diols starting from cheap aldehydes. The carboligation of two aldehydes using Pseudomonas fluorescens benzaldehyde lyase and subsequent oxidoreduction with Ralstonia sp. alcohol dehydrogenase yielded 1‐phenylpropane‐1, 2‐diol [(1R, 2R)‐PPD] in concentrations of up to 339 mM and excellent enantiomeric and diastereomeric excesses >99 %. Therefore, the combination of whole‐cell catalysis and teabag modularisation allows cheap, easy‐to‐apply and efficient catalyst preparation to test enzyme combinations and optimal reaction conditions up to the preparative scale. By circumventing catalyst purification and immobilisation, and enabling high substrate loadings compared to those in aqueous systems, efficient production of a chiral diol with extraordinarily high product concentrations can be achieved.